Utilization pattern of drugs among patients attending geriatric outpatient department in a tertiary care hospital in Kashmir - Tabassum, Rehana; Hafiz, Umar; Hussain, Syed Sajad; Shah, Asma; Shabir, Afshan (International Journal of Research in Medical Sciences, 2019)
Background: Quality and safety of prescribing in older people remains a global healthcare concern and inappropriate prescribing is a major public health issue because of its direct association with morbidity, mortality and wastage of health resources in this age group. Very limited data is available on the drug utilization pattern in geriatric population and the present study was carried out to see the prescription pattern in geriatric population in this part of the world. Methods: The present study was conducted by the department of pharmacology in outpatient department of geriatrics in a tertiary care centre to look into the prescription pattern among geriatric age group. Results: A total of 237 prescriptions were collected, out of which 108 (45.56%) were males and 129 (54.44%) were females. The majority of the patients were in the age group of 60-69 years (n=141, 59.5%). The most commonly found comorbidity was hypertension (63.29%) and antihypertensive agents (74.68%) were the most frequently prescribed class of drugs. Calcium (37.57%), budesonide (32.91%), thyroxine (27.84%) and pantoprazole (25.31%) were the most common individual drugs prescribed. Conclusions: Like other studies on geriatric population polypharmacy was also observed in the present study and periodic therapeutic audit is essential to ensure rational medicine use.